Teacher Competency Training in Developing Construct 3 Educational Games for the English MGMP of Lima Puluh Kota - Hendriyani, Yeka; Effendi, Hansi; Asnur, Lise (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2026)
This community service activity aimed to improve the competencies of English MGMP teachers in Lima Puluh Kota Regency in developing Construct 3-based educational games. The partners’ main problems were limited information technology skills, minimal experience in designing interactive learning media, and the dominant use of conventional media such as textbooks, whiteboards, and simple presentations. The solution offered was a structured training program covering the introduction to educational game concepts, interface design, game development using Construct 3, as well as testing and independent assignments. The implementation method included preparation, face-to-face training, online mentoring, and evaluation using pre-tests, post-tests, observations, and perception questionnaires. The results showed that the training helped teachers understand the workflow of developing game-based learning media, improved their skills in using Construct 3, and encouraged the creation of more interactive learning media products. This activity demonstrates that practice-based training and continuous mentoring are effective in strengthening teachers’ capacity to produce digital learning media that are relevant to students’ needs.